The Impact of the COVID-19 Pandemic on an Israeli Acute Care Surgery Unit: Fewer Patients, More Disease. Issue 12 (December 2022) - Maman, Yossi; Lee Goldstein, Adam; Neeman, Uri; Lessing, Yonatan; Orbach, Lior; Sirhan, Saad; Falk, Ela; Lahat, Guy
Background: The COVID-19 pandemic has transformed and affected every aspect of health care. Like any catastrophic event, the stress on hospitals to maintain a certain level of function is immense. Acute surgical pathologies cannot be prevented or curtailed; therefore, it is important to understand patterns and outcomes during catastrophes in order to optimize care and organize the health care system. Methods: In a single urban tertiary care center, a retrospective study examined the first complete lockdown period of Israel during the COVID-19 pandemic. This was compared to the same time period the previous year. Results: During the pandemic, time to hospitalization was significantly decreased. There was also an overall reduction in surgical admissions yet with a higher percentage being hospitalized for further treatment (69.2% vs 23.5%). The patients admitted during this time had a higher APACHE-II score and Charlson comorbidity index score. During the pandemic, time to surgery was decreased, there were less laparoscopic procedures, and more RBC units were used per patient. There were no differences in overall complications, except when sub-analyzed for major complications (9.7% vs 6.3%). There was no significant difference in overall in-house mortality or morbidity. Length of hospitalization was significantly decreased in the elderly population during the pandemic. Conclusion: During the COVID-19 pandemic, despite a significantly less number of patients presenting to the hospital, there was a higher percentage of those admitted needing surgical intervention, and they were overall sicker than the previous year.